The Australian Primary Care Collaboratives Program: improving diabetes care. Issue 11 (16th June 2012) - Knight, Andrew W; Ford, Dale; Audehm, Ralph; Colagiuri, Stephen; Best, James
Abstract : Problem: Diabetes is a major, growing health problem often managed in primary care but with suboptimal control of risk factors. Design: A large-scale quality improvement collaborative implemented in seven waves. Setting: General practices and Aboriginal medical services across Australia. Key measures for improvement: Percentage of patients in each health service with haemoglobin A1C (HbA1C), total cholesterol and blood pressure at target. Strategy for change: Health services attended three 2-day workshops, separated by 3-month activity periods and followed by 12 months of further improvement work. Local collaborative program managers supported teams to report measures and plan/do/study/act (PDSA) cycles monthly. Health services received feedback about changes in their measures in comparison with their wave. Effects of change: 743 health services participated in seven waves between 2004 and 2009 serving approximately 150 000 people with diabetes. Mean numbers of patients at target HbA1c levels improved by 50% from 25% at baseline to 38% at month 18. Lipid and blood pressure measures showed similar improvement. Lessons learnt: Engagement in the Program and results demonstrated that the collaborative methodology is transferable to Australian primary care. The results may reflect improved data recording and disease coding, and changes in clinical care. Internal evaluation should be built into improvement projects from the start to facilitate improvements and reporting. Enthusing, training and resourcing practice teams appeared to be the key to rapid change. Local support of practice teams was instrumental in improvement. Early investment to facilitate automatic measure collection ensured good data reporting.